Respons Pemberian Pupuk Organik Basimbah Tani Terhadap Pertumbuhan Padi Gogo Varietas Inpago 8 - Sadinar Pohan; Novilda Elizabeth Mustamu; Fitra Syawal Harahap; Badrul Ainy Dalimunthe (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2022)
SADINAR POHAN : The Response of Farmer’s Basimbah Organic Fertilizer to the Growth of Upland Rice of Inpago 8 Varieties, supervised by Ibu NOVILDA ELIZABETH AMUSTAMU,S.,PT.M.Si and Bapak FITRA SYAWAL HARAHAP.SP.,M.Agr. This study aims to study the Response of Farmer’s Basimbah Organic Fertilizer to the Growth of Upland Rice of Inpago 8 Varieties. This research was conducted in the village of promise, Bilahbarat district, Labuhanbatu Regency from March 2021 to June 2021. The experimental method used wan non-factorial and 3 replications. The data obtained were analyzed using a variance test and continued with the Duncan distance test. The results showed that the application of farmer basimbah organic fertilizer at a dose of 5 g/polybaeng was able to increase plants aged 5-7 wap, plat heigt, number of tillers, root vilume. The response of the application of basimbah organic fertilizer has a significant effect on all parameters.Keywords : upland rice, organic fertilizer, inpago 8